Pengaruh Pengungkapan Corporate Social Responsibility Pada Nilai Perusahaan Dengan Manajemen Laba Sebagai Variabel Moderasi - Sabatini, Kalvarina; Sudana, I Putu (Jurnal Ilmiah Akuntansi dan Bisnis, 2019)
The study aims to determine the effect of Corporate Social Responsibility  disclosure on firm value and to determine earnings management moderate the  effect of Corporate Social Responsibility disclosure on firm value. Agency theory  used in this research as the grand theory. The population in this study are  companies listed in the Business Index 27 in 2014–2016, which are listed on  Indonesia Stock Exchange. Sample in this study was taken using purposive  sampling technique. The analysis technique used in this study is moderated  regression analysis technique. The results show that Corporate Social  Responsibility has negative and significant effect on firm value. In addition  earnings management has no significant effect on Corporate Social Responsibility  disclosure on firm value. Theoretical implication shows that these results are in  line with the signaling theory but contradictory with agency theory. On the other  hand, practical implications of this research can be taken into consideration for  potential investors and investors in making decisions by looking at CSR  information which disclosed by the company . Keywords : CSR, earnings management, firm value